2015
DOI: 10.4055/cios.2015.7.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Septic Arthritis of Hip in Infants and Neonates: Minimum 5-Year Follow-up

Abstract: BackgroundThe authors conducted the present study to identify clinical and radiological prognostic factors in infants and neonates with septic arthritis of the hip.MethodsThe authors retrospectively reviewed the records of 31 patients with septic arthritis of the hip. All of the patients were younger than 18 months old. Follow-up periods ranged from 5 to 17 years. The following potential variables for predicting the prognosis were included in the assessment: gender, age, underlying diseases, duration of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
0
43
1
Order By: Relevance
“…This is in keeping with reported unsatisfactory outcomes ranging from 16.1% to 27%. 7 This may reflect the younger patient population studied, <18 months. In our study, there was no clear association between treatment method and poor long-term outcomes, this may be due to low numbers of patients treated with methods other than arthrotomy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is in keeping with reported unsatisfactory outcomes ranging from 16.1% to 27%. 7 This may reflect the younger patient population studied, <18 months. In our study, there was no clear association between treatment method and poor long-term outcomes, this may be due to low numbers of patients treated with methods other than arthrotomy.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,14,15 Morrey et al 6 in 1975 reported unsatisfactory outcomes in 50% of patients with hip septic arthritis versus 12% with other joint involvement; these higher unsatisfactory outcomes may reflect advances in identification and treatment since 1975. This is in keeping with reported unsatisfactory outcomes ranging from 16.1% to 27%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations